The social dimension of the occurrence of disease: II - the positiveness of reaction to Wasserman and VDRL tests among draftees in S. Paulo State (Brazil), from 1972 to 1978 - Goldenberg, Paulete; Pardo, Rosa Maria; Neto, Dalva Regina; Ribeiro, Sandra Aparecida; Pernambuco, Maurício; Iunes, Magid (Revista de Saúde Pública, 1982)
Following up the historical series started in 1968, the collection of data from 1972 to 1978 has shown that in the long run, in spite of oscillations, there were no significant variations of the coefficients of positiveness of the Wasserman and VDRL reactions in the boys recruited to the Army in the Capital. In the hinterland the raising on the coefficients' rates, from 1973 on, reverting the tendency previously observed, brought these rates near to those of the Capital. The study of the sub-samples showed the presence of larger proportions of positiveness among the recruits enlisted in the Capital as compared to those in the hinterland, independente of origin which may suggest some similarity to epidemiological reports from developed countries. On the other hand, among the recruits enlisted in the Capital there were larger proportions of positiveness among those born in other States of the country, which could be regarded as evidence of the presence of illness associated with proverty or under-development. In this connection, attention is called by the authors to the epidemiological peculiarities of the illness in view of the singularity of the respective social organizations at a given historical moment.